Development Of Workholding Device For Loaded PCB Cutting Process - Mohd Hafiszuddin, Mohd Puaad (UTeM, 2009)
Workholding is a device that hold, grip, chuck, support and locates a workpiece to perform a manufacturing process. Suppose that for routing process of the printed circuit board (PCB), which is one of the method of the depanelization of PCB, the PCB must be hold properly so that the PCB will not slipped during the routing process which can lead to PCB damage. However, due to the condition of the PCB which is warped after the soldering process, the location of the locating support of the workholding must be determined so that it can fully support the PCB. The method used to determine the location of the locating support is known as stress deformation analysis.